MUSEUS DA GRANDE VITÓRIA (ES): LAZER, SOCIALIZAÇÃO, POSSIBILIDADES DE CONHECIMENTO E IDENTIDADE CULTURAL - Felipe, Eline Tosta (2021)
Leisure in museums reveals itself as a possibility of reflexive experience, sociability and a reference of identity. The museological institutions propose to integrate heritage and social dynamics, serving from the local community as well as tourists, instigating geographic understanding. Therefore, the current research aims to clarify the importance of museums in the Metropolitan Region of Greater Vitória (ES / Brazil) for the exercise of leisure. In this process, the methods of observation in loco, semi-structured alterations and collection of testimonials with managers, employees, volunteers and visitors were used. It can be concluded that the researched museums seek to integrate their communities, promoting encounters with local identity, knowledge and socialization among their visitors.